Engineering oxygen vacancy in (001)-dominated TiO2 for enhanced CH4 photocatalytic conversion. (December 2022) - Ju, Tangtong; Tang, Hailong; Wang, Meiling; Ma, Yongqing; Sun, Xiao; Wang, Min; Zheng, Ganhong; Tang, Haibin
Highlights: (001)-dominated ultrathin TiO2 nanosheets (NSs) with oxygen vacancy were prepared. The TiO2 NSs were used for CH4 photocatalytic conversion with H2 O2 as the necessary oxidant. Oxygen vacancy largely lowered the reaction energy of CH4 →CH3 *+ H *. The highest C1 products yield was 5.95 mmol g −1 h −1 with selectivity of 99.03%. The yield is comparable to the record using binary/ternary catalysts with metals. Graphical abstract: Image, graphical abstract Abstract: Photooxidation of methane to high valued C1 liquid products with both high yield and selectivity against overoxidation has been a huge challenge. In this work, (001)-dominated ultra-thin TiO2 nanosheets with plenty of oxygen vacancies (Ov ) were mass produced by simple hydrothermal and annealing treatments, and used for photocatalytic oxidation of CH4 into C1 products (mainly HCHO, CH3 OOH and HCOOH) with H2 O2 as the necessary oxidant. For the optimal catalyst with the largest Ov ratio, the highest C1 products yield of 5.95 mmol g −1 h −1 was achieved within 2 h, accompanied by a high C1 selectivity of 99.03%, comparable to the current yield record over precious-metal based binary/ternary catalyst. In-situ electron spin resonance, in-situ Fourier Transform Infrared Spectroscopy and mass spectra combined with density functional theory calculations were used for comprehensive clarification of the underlying reaction mechanism. Ov on TiO2 -(001) face largely lowered the energy required for CH bond cleavage of CH4, which was the rate-determinate reaction during CH4 photooxidation. Then formed *CH3 went through distinct reaction routes of Ti-OOH+Ti-CH3 →Ti–OCH3 +Ti-OH→HCHO, thus achieving high yield and selectivity for the main primary product of HCHO (65.7%).